Ecobiology of Anaphothrips obscurus, a new dweller of citrus orchards brought in by more sustainable pest management practices. (29th May 2017) - Gómez‐Martínez, María A.; Aguilar‐Fenollosa, Ernestina; Jaques, Josep A.; Pina, Tatiana
Abstract: The abundance and frequency of Anaphothrips obscurus (Thysanoptera: Thripidae) increased in a cover of Festuca arundinacea (Poaceae) when this plant was used to improve the biological control of the clementine key pest Tetranychus urticae (Acari: Tetranychidae). To unveil the ecological role of A. obscurus in this system, we re‐explored field data and performed laboratory studies aiming to determine its demographic parameters and feeding habits, as well as its role as a prey of predatory mites (Acari: Phytoseiidae) occurring in the Spanish citrus agreoecosystem. Field studies indicate that T. urticae populations decreased, whereas those of A. obscurus and phytoseiids, as a whole, increased. Reproductive and demographic parameters of macropterous and brachypterous morphs of A. obscurus were different and confirmed the host status of F. arundinacea . Anaphothrips obscurus could compete with T. urticae as a result of its higher intrinsic rate of increase in F. arundinacea . However, A. obscurus zoophagy on T. urticae eggs and the host status of citrus can be discarded. Anaphothrips obscurus can be a prey for Euseius stipulatus, Neoseiulus barkeri and Neoseiulus californicus (three phytoseiids preying on T. urticae ), suggesting that apparent competition between A. obscurus and T. urticae could occur in citrus orchards.